Gambaran Aktivitas Fisik Lansia Hipertensi di Posyandu Lansia Wonoboyo Wonogiri - Nuri Nita Sari; Eska Dwi Prajayanti (PT Pustaka Cendekia Publisher, 2026)
The prevalence of elderly individuals with hypertension continues to rise alongside global cardiovascular disease rates, including in Indonesia. Declining physical activity due to aging and disease conditions makes hypertensive elderly more vulnerable to complications. This study aims to describe the physical activity profile of elderly hypertensive patients at Posyandu Lansia Wonoboyo, Wonogiri. This research employed a descriptive quantitative design with a survey approach involving 80 registered elderly hypertensive patients at the posyandu, selected using purposive and simple random sampling. The research instruments consisted of the Physical Activity Scale for the Elderly (PASE) questionnaire and respondent characteristic questionnaires. Data were analyzed using frequency distribution and percentage techniques through univariate analysis with SPSS program assistance. The results showed that most respondents had good physical activity levels (68.8%), while a small portion fell into the poor category (31.3%). The majority of elderly were aged 60–69 years, female, and had experienced hypertension for 1–5 years. This study concludes that physical activity among elderly hypertensive patients at Posyandu Lansia Wonoboyo is generally adequate, although some groups still exhibit minimal activity. Structured intervention programs are needed to maintain or enhance physical activity among hypertensive elderly.